1998
DOI: 10.1007/s100249900042
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic Neuroectodermal Tumor of Infancy: A Molecular Genetic Study

Abstract: Melanotic neuroectodermal tumor of infancy is a rare but well-recognized entity in pediatric pathology. However, the relationship of this tumor to other pediatric small cell tumors with neuroectodermal features (such as neuroblastoma, Ewing sarcoma/peripheral primitive neuroectodermal tumor, and desmoplastic small round cell tumor) is undetermined. Molecular genetic studies of melanotic neuroectodermal tumor of infancy have not been reported. We studied three typical cases of melanotic neuroectodermal tumor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…320,326 Despite the morphologic similarity of the small cells to neuroblastic cells, molecular markers for neuroblastoma, including N-myc amplification and 1p deletion, are absent, as are the translocations seen in Ewing's sarcoma and desmoplastic small round cell tumor. 327 Most cases behave in a benign fashion, although one epididymal tumor in a 17-month old did metastasize to retroperitoneal lymph nodes, 328 and another in a 6-month old invaded the lymphatics but had a clinically benign course. 323 It has been suggested that the uncommon cases of maxillary melanotic neuroectodermal tumor that behave aggressively may be prospectively recognized by elevated mitotic rates and high proliferative fractions, as assessed by Ki-67 staining.…”
Section: Melanotic Neuroectodermal Tumor (Retinal Anlage Tumor)mentioning
confidence: 98%
“…320,326 Despite the morphologic similarity of the small cells to neuroblastic cells, molecular markers for neuroblastoma, including N-myc amplification and 1p deletion, are absent, as are the translocations seen in Ewing's sarcoma and desmoplastic small round cell tumor. 327 Most cases behave in a benign fashion, although one epididymal tumor in a 17-month old did metastasize to retroperitoneal lymph nodes, 328 and another in a 6-month old invaded the lymphatics but had a clinically benign course. 323 It has been suggested that the uncommon cases of maxillary melanotic neuroectodermal tumor that behave aggressively may be prospectively recognized by elevated mitotic rates and high proliferative fractions, as assessed by Ki-67 staining.…”
Section: Melanotic Neuroectodermal Tumor (Retinal Anlage Tumor)mentioning
confidence: 98%
“…Increased alpha-fetoprotein levels and positive staining for the c-myc antigen, characteristic of other neural crest tumours, has also been described (5,27,29,33,34). Despite these microscopic and immunohistochemical similarities, there are no shared genetic changes linking MNTI with the other neuroectodermal tumours (14,35).…”
Section: Discussion and Literature Reviewmentioning
confidence: 95%
“…They detected MYCN gene amplification and deletion of 1p in all 3 cases and presence of the t(11;22)(q24;q12) and the t(11;22)(p13;q12) translocations in 2 of 3 cases . But, there was no genetic basis to link melanotic neuroectodermal tumour of infancy to neuroblastoma, Ewing sarcoma/peripheral primitive neuroectodermal tumour, or desmoplastic small round cell tumour [14].…”
Section: Discussionmentioning
confidence: 99%